Treatment of osteomyelitis of the lingula: Case report. (6th May 2021) - Tran, Truc; Coleman, Olivia; Sproat, Chris
Abstract: Osteomyelitis of the jaw is an uncommon condition in healthy individuals and is usually associated with immunocompromised patients. We report a rare case of a healthy patient of no significant medical background who developed osteomyelitis of the lingula following routine dental extractions. The management of the case has been described.